2011
DOI: 10.1002/btpr.499
|View full text |Cite
|
Sign up to set email alerts
|

Improved particle counting and size distribution determination of aggregated virus populations by asymmetric flow field‐flow fractionation and multiangle light scattering techniques

Abstract: A method using a combination of asymmetric flow field-flow fractionation (AFFFF) and multiangle light scattering (MALS) techniques has been shown to improve the estimation of virus particle counts and the amount of aggregated virus in laboratory samples. The method is based on the spherical particle counting approach given by Wyatt and Weida in 2004, with additional modifications. The new method was tested by analyzing polystyrene beads and adenovirus samples, both having a well-characterized particle size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…However, there is evidence that virus samples contain virus particle-associated nuclease-resistant RNA, which can artificially increase the number gene copies (Dovas et al, 2010; Wei et al, 2007). It is also possible that FFF-MALS quantitation may underestimate the number of virus particles counted, due to increased error when virus is eluted within the aggregate fraction (McEvoy et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that virus samples contain virus particle-associated nuclease-resistant RNA, which can artificially increase the number gene copies (Dovas et al, 2010; Wei et al, 2007). It is also possible that FFF-MALS quantitation may underestimate the number of virus particles counted, due to increased error when virus is eluted within the aggregate fraction (McEvoy et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…By measuring the intensity and angular dependency of the scattered light, it is possible to deduce the radius of the particles and subsequently calculate the number of particles per volume. FFF-MALS was recently applied to characterize influenza virus particles (McEvoy et al, 2011; Wei et al, 2007). Virus particle quantitation by FFF-MALS correlated well with results from other methods, including size exclusion chromatography (SEC-MALS), qRT-PCR, transmission electron microscopy (TEM), and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…By first fractionating the sample based on vesicle size, A4F/MALS circumvents the vesicle size dependence of scattered light in DLS and NTA. 3035 Quantitative measurements of vesicle number concentrations are attainable with an appropriate model for the single-vesicle scattering function that contains an accurate refractive index profile for the vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, perhaps only ES-DMA (Cledat et al 2004; Guha et al 2012; Jennerjohn et al 2010; McEvoy et al 2011; Pease 2012; Pease et al 2009a, 2009b, 2010b; Tsai et al 2010, 2011a, 2011b) is capable of counting particles from < 5 nm to approximately 1 μm in a manner largely independent of the material’s properties. Other available methods, such as commercial micro channel resonators (Burg et al 2007; Lau et al 2011) (Table 2) and nanoparticle tracking analysis (see Supplemental Material, “Non-Imaging Particle Counting Techniques,” pp.…”
Section: Current Status and Knowledge Gaps In Nano-object Count Metromentioning
confidence: 99%
“…However, extreme care and highly skilled workers are required to properly apply these methods. McEvoy et al (2011) recently demonstrated that AFFF combined with multi-angle light scattering (MALS) can determine viral particle number concentrations with an error of < 5%. Tsaiet al (2011a) also independently demonstrated a linear correlation with AFFF-equipped MALS intensity and nanoparticle number counts generated by ES-DMA for 10- and 30-nm gold nanoparticles, as well as larger-sized agglomerates.…”
Section: Current Status and Knowledge Gaps In Nano-object Count Metromentioning
confidence: 99%